Hypertension screening, awareness, treatment, and control in India: a nationally representative cross-sectional study among individuals aged 15 to 49 years - Prenißl, Jonas; Bischops, Anne Christine; Bärnighausen, Till (PLoS medicine, 2019)
Background Evidence on where in the hypertension care process individuals are lost to care, and how this varies among states and population groups in a country as large as India, is essential for the design of targeted interventions and to monitor progress. Yet, to our knowledge, there has not yet been a nationally representative analysis of the proportion of adults who reach each step of the hypertension care process in India. This study aimed to determine (i) the proportion of adults with hypertension who have been screened, are aware of their diagnosis, take antihypertensive treatment, and have achieved control and (ii) the variation of these care indicators among states and sociodemographic groups. Methods and findings We used data from a nationally representative household survey carried out from 20 January 2015 to 4 December 2016 among individuals aged 15-49 years in all states and union territories (hereafter “states”) of the country. The stages of the care process—computed among those with hypertension at the time of the survey—were (i) having ever had one’s blood pressure (BP) measured before the survey (“screened”), (ii) having been diagnosed (“aware”), (iii) currently taking BP-lowering medication (“treated”), and (iv) reporting being treated and not having a raised BP (“controlled”). We disaggregated these stages by state, rural-urban residence, sex, age group, body mass index, tobacco consumption, household wealth quintile, education, and marital status. In total, 731,864 participants were included in the analysis. Hypertension prevalence was 18.1% (95% CI 17.8%-18.4%). Among those with hypertension, 76.1% (95% CI 75.3%-76.8%) had ever received a BP measurement, 44.7% (95% CI 43.6%-45.8%) were aware of their diagnosis, 13.3% (95% CI 12.9%-13.8%) were treated, and 7.9% (95% CI 7.6%-8.3%) had achieved control. Male sex, rural location, lower household wealth, and not being married were associated with greater losses at each step of the care process. Between states, control among individuals with hypertension varied from 2.4% (95% CI 1.7%-3.3%) in Nagaland to 21.0% (95% CI 9.8%-39.6%) in Daman and Diu. At 38.0% (95% CI 36.3%-39.0%), 28.8% (95% CI 28.5%-29.2%), 28.4% (95% CI 27.7%-29.0%), and 28.4% (95% CI 27.8%-29.0%), respectively, Puducherry, Tamil Nadu, Sikkim, and Haryana had the highest proportion of all adults (irrespective of hypertension status) in the sampled age range who had hypertension but did not achieve control. The main limitation of this study is that its results cannot be generalized to adults aged 50 years and older—the population group in which hypertension is most common. Conclusions Hypertension prevalence in India is high, but the proportion of adults with hypertension who are aware of their diagnosis, are treated, and achieve control is low. Even after adjusting for states’ economic development, there is large variation among states in health system performance in the management of hypertension. Improvements in access to hypertension diagnosis and treatment are especially important among men, in rural areas, and in populations with lower household wealth.